The Effectiveness of Thematic Learning through the Cooperative Learning Approach of Team Accelerated Instruction (TAI) in Grade IV of SDN Cengkareng Barat 11 - Fadli, Muhammad Rijal; Fatonah, Khusnul; Afwan, Bahtiar; Qurrotu’ain, Rofifah (Honoli of Journal Primary Teacher Education, 2025)
This study aimed to improve motivation and academic achievement of fourth-grade students at SDN Cengkareng Barat 11 Jakarta by applying the Cooperative Learning model, Team Accelerated Instruction (TAI), in thematic learning on Theme 8: "Our Environment, Our Friend." Using Classroom Action Research across three cycles, data on lesson plan quality, teacher performance, student motivation, and achievement were collected. Results showed significant improvements: lesson plan quality rose from 70% to 93%, teacher performance from 74% to 96%, student motivation from 70% to 94%, and students meeting Minimum Mastery Criteria increased from 60% to 94%. These findings confirm TAI’s effectiveness in enhancing learning quality, motivation, and achievement, recommending its use in primary education for more active and collaborative learning.